A comprehensive review of endpoint detection in chemical mechanical planarisation for deep-submicron integrated circuits manufacturing. (1st January 2003) - Hocheng, H.; Huang, Y.-L.
As the number of metal levels and the wafer size increase, the need for global planarity across the wafer becomes more crucial. Chemical mechanical planarisation (CMP) is considered the key technique to achieve this goal. Accurate in situ end point detection and monitoring method can reduce the product variance, improve the yield and throughput. During CMP process, the wafer is brought downward against the polishing pad completely. The monitoring of the wafer polishing in such a configuration becomes a difficult task. Many methods have been proposed in the past years, including the optical, electrical, acoustical/vibrational, thermal, frictional, chemical/electrochemical methods and others, which are critically reviewed in this study. The mainstream of the industrial application and the future trend are investigated.